Digital Transformation and Innovative Business Models for Attaining Sustainable Competitive Advantage : Systematic Literature Review - Syakur, Abd.; Zuhroh, Diana; Harmono, Harmono; Bella Ayu, Roro (Moneter: Jurnal Keuangan dan Perbankan, 2025)
This systematic literature review explores the convergence of digital transformation and innovative business models in achieving a sustainable competitive advantage. As organizations increasingly adopt digital technologies such as artificial intelligence (AI), cloud computing, and the Internet of Things (IoT), they are transforming their operations and enhancing customer experiences. Simultaneously, there is a growing emphasis on integrating sustainability into business strategies, with a focus on economic, environmental, and social sustainability. This review highlights the critical role of business model innovation in leveraging digital tools to create value while addressing the environmental and social impacts of business activities. The findings underscore the importance of combining digital transformation with sustainable practices to drive long-term growth, improve operational efficiency, and meet evolving regulatory and consumer expectations. Ultimately, businesses that successfully integrate these two forces are better positioned to thrive in an increasingly competitive and eco-conscious market.